Bahasa Inggris - Akbar Novan Dwi Saputra; Dicky Moch Rizal; Nandia Septiyorini; Muhammad Nurhadi Rahman (Universitas Andalas, 2024)
Background : Platelet-rich plasma (PRP) is an autologous, self-blood product, an anticoagulated blood product generated by the centrifugation method of whole blood that primarily contains platelets at amounts up to 5 times those found in physiologic platelet concentrations. The use of PRP in pelvic floor reconstruction surgery is becoming much more common. Objective : To determine the efficacy of PRP on pelvic floor reconstruction surgery, we will synthesize the available research on the use of PRP for pelvic floor disorders.; Methods: This review was conducted on research articles in PubMed, Proquest, EBSCO, and ScienceDirect databases published between January 2010 – December 2023 regarding the use of PRP for pelvic floor reconstruction surgery. All primary research in humans, case reports and case series will be included to evaluate the outcome of PRP as an adjunct to conventional surgery in treating pelvic floor disorders; Results: A total of five articles were chosen for review. Every article makes use of PRP in pelvic floor reconstruction surgery. Conclusions: This review offers actual evidence of PRP's efficacy in pelvic floor reconstruction surgery. This is a new approach, and the findings of this study are expected to inform clinical practice and ongoing research focused on improving the outcome of pelvic floor disorders treatment. Trial registration number: osf.io/gyr72